2014
DOI: 10.3389/fpls.2014.00100
|View full text |Cite
|
Sign up to set email alerts
|

The diverse roles of FRO family metalloreductases in iron and copper homeostasis

Abstract: Iron and copper are essential for plants and are important for the function of a number of protein complexes involved in photosynthesis and respiration. As the molecular mechanisms that control uptake, trafficking and storage of these nutrients emerge, the importance of metalloreductase-catalyzed reactions in iron and copper metabolism has become clear. This review focuses on the ferric reductase oxidase (FRO) family of metalloreductases in plants and highlights new insights into the roles of FRO family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 64 publications
1
64
0
2
Order By: Relevance
“…For instance, the family containing the Arabidopsis FERRIC REDUCTION OXIDASE4 (FRO4) and FRO5 genes include root-expressed genes from all vascular plant species tested except rice and maize. This implies the loss of this root hair-related gene activity during monocot evolution, perhaps associated with distinct strategies used by grasses for iron acquisition (Jain et al, 2014).…”
Section: Rice Root Hair Development Genesmentioning
confidence: 99%
“…For instance, the family containing the Arabidopsis FERRIC REDUCTION OXIDASE4 (FRO4) and FRO5 genes include root-expressed genes from all vascular plant species tested except rice and maize. This implies the loss of this root hair-related gene activity during monocot evolution, perhaps associated with distinct strategies used by grasses for iron acquisition (Jain et al, 2014).…”
Section: Rice Root Hair Development Genesmentioning
confidence: 99%
“…For instance, FERRIC REDUCTION OXIDASE4 (FRO4) and FRO5 (AT5G23980 and AT5G23990), which play important roles in the uptake of iron and copper from the soil (Bernal et al, 2012;Jain et al, 2014), were identified. Additionally, a vacuolar iron transporter and a metal transporter (VACUOLAR IRON TRANSPORTER-LIKE5 [AT3G25190] and ZRT/ IRT-LIKE PROTEIN2 [AT5G59520]) were classified as potential tolerance genes.…”
Section: Natural Variation In Submergence Tolerance Is Associated Witmentioning
confidence: 99%
“…Both transcription factors (TFs) regulate gene expression during Cu deficiency through binding to Cu deficiency-responsive elements (59-GTAC-39) in promoters of their targets (Sommer et al, 2010;Yamasaki et al, 2009;Quinn et al, 2000;Birkenbihl et al, 2005;Garcia-Molina et al, 2014;Kropat et al, 2005). Recent transcriptome analyses revealed that SPL7 is required for the expression of the iron (Fe)/Cu reductase oxidases, FRO4 and FRO5, and several Cu transporters, including members of the copper transporter family, COPT1 and COPT2, that together constitute the high-affinity Cu uptake system (Bernal et al, 2012;Gayomba et al, 2013;Jung et al, 2012;Yamasaki et al, 2009;Jain et al, 2014). Among other SPL7-regulated genes are COPT6, members of the yellow stripe-like transporter family, YSL2 and YSL3, and the Cu chaperone CCH, which together contribute to Cu transport to photosynthetic tissues and Cu remobilization from sources to sinks upon senescence (Bernal et al, 2012;Gayomba et al, 2013;Jung et al, 2012;Yamasaki et al, 2009;Chu et al, 2010;Himelblau et al, 1998;Mira et al, 2001;Himelblau and Amasino, 2001).…”
Section: Introductionmentioning
confidence: 99%